Assessment of the effect of ofatumumab on cardiac repolarization. (21st August 2014) - Jewell, Roxanne C.; Laubscher, Kevin; Lewis, Eric; Fang, Lei; Gafoor, Zarina; Carey, Jodi; McKeown, Astrid; West, Sarah; Wright, Oliver; Sedoti, Donna; Dixon, Iestyn; Hottenstein, Charles Scott; et al.
Abstract Ofatumumab is a human monoclonal antibody that binds to a unique CD20 epitope on the surface of B lymphocytes, resulting in efficient lysis of CD20‐expressing cells via complement‐dependent cytotoxicity and antibody‐dependent cell‐mediated cytotoxicity. The potential effect of ofatumumab on cardiac repolarization and the relationship between ofatumumab concentration and change in corrected QT interval (ΔQTcF) were evaluated in data from three clinical trials in 82 patients with chronic lymphocytic leukemia receiving ofatumumab alone (n = 14), ofatumumab with chemotherapy (n = 33), and chemotherapy alone (n = 35). Because of ofatumumab accumulation, baseline QTcF interval was recorded prior to the first infusion for each patient. No patient had a post‐baseline QTcF interval >480 milliseconds or a ΔQTcF >60 milliseconds; five patients (four on ofatumumab) had a ΔQTcF between 30 and 60 milliseconds. At cycle 6 (week 21; 308 μg/mL), there was an increase in QTcF in patients on ofatumumab treatment, with an estimated between‐treatment difference (90% CI) of 12.5 (4.5, 20.5) milliseconds. However, at the visit with the highest median concentration (week 8; 1386 μg/mL), median ΔQTcF was 4.8 milliseconds. There was no significant relationship between ofatumumab plasma concentration and ΔQTcF. Ofatumumab did not have a clinically significant effect on cardiac repolarization.